Is Functional Near Infrared Spectroscopy (fNIRS) Appropriate for your Research?. (September 2016) - Mehta, Ranjana K.; Ayaz, Hasan; McKendrick, Ryan; Izzetoglu, Kurtulus; Willems, Ben; Ziegler, Matthias
Functional near infrared spectroscopy (fNIRS) is an emerging neuroimaging technique that has found home in various human factors and ergonomics applications. Why fNIRS? Is it better than EEG or fMRI? Is it an appropriate neuroimaging technique for my research/application? What are the methodological considerations for fNIRS analyses? This panel discussion is aimed at answering these questions, among others, when panelists from varied human factors and ergonomics applications discuss how they employ fNIRS in their investigations.